The Importance of Creative Industry Agglomerations in Explaining the Wealth of European Regions - Blanca De Miguel Molina; José Luis Hervás Oliver; Rafael Boix Domenech; María De Miguel Molina (European Regional Science Association (ERSA), 2011)
This paper examines the existence of regional agglomerations of manufacturing, service and creative industries, the relationship between these industries and the wealth of regions and their industrial structure. Through an analysis of 250 European regions, three important conclusions can be inferred from the results obtained in this paper. The first is that creative industries play an important role in the wealth of a region. The second is that the most creative regions are characterized by having more high-tech manufacturing industries than the rest of the regions although the number of low-tech manufacturing firms is similar. Lastly, the industrial structure of each region has a greater influence on regional wealth than the existence of industrial agglomerations. The importance of this paper resides in the fact that up until now no analysis has demonstrated that creative industries are the most important industries in regional wealth.
Keywords: 330